The fishermen - Obioma, Chigozie, 1986- (New York : Little, Brown and Company, 2015)
In a Nigerian town in the mid-1990s, four brothers encounter a madman whose mystic prophecy of violence threatens the core of their close-knit family.
Keywords: Brothers -- Fiction; Brothers -- Fiction; Nigeria -- Fiction; Nigeria -- Fiction